Impact of Corruption on Bank Profitability in Developing Countries: An Empirical Evidence from the Asian Banking Sector - Wang, Yafei (2017)
This study attempts to analyse econometrically the impact of corruption on bank profitability in 12 Asian developing countries, and provides additional empirical evidences on topic of bank profitability determinants. By using a balanced panel data set comprising 805 observations of 161 individual banks operating in 12 Asian developing countries over the 2012-2016 time period and fixed effects regression, the results reveal that corruption has a significant and positive impact on bank profitability in developing countries. Among other variables, size, asset quality, capital adequacy, expense management are negatively related to bank profitability while stock market development and GDP growth are positively related at significance. The results lend some credence to implications that banks are thriving from corruption in developing countries.